Learning Interest : How Does The Experimentation of The Game-Based Learning Models? - Anggraini Pratiwi; Kiki Nazira; Michellona Erza Pramugita; Meri Aryani; Muhammad Arif Sobar; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
Islamic Religious Education (IRE) plays a pivotal role in fostering knowledge and enhancing students’ personal development. However, its implementation faces several major challenges, notably the low level of student interest and active participation in IRE subjects. This is particularly evident in the aspect of student engagement, which reached only 21% based on the results of a preliminary survey. The purpose of this study is to evaluate the effectiveness of implementing the Game-Based Learning (GBL) model in increasing students’ learning interest in IRE at SMP Negeri 23 Bandar Lampung. To address this issue, the study employed a quantitative approach with a quasi-experimental design. Data analysis techniques included normality testing, homogeneity testing, and hypothesis testing using both the Independent Samples t-Test and the non-parametric Mann-Whitney U test. The research findings indicate that the GBL model significantly enhances students’ learning interest. The application of Game-Based Learning (GBL) has proven effective in improving students’ enthusiasm for learning IRE at SMP Negeri 23 Bandar Lampung, fostering a learning environment that is both enjoyable and participatory. These findings imply the necessity of integrating game-based approaches into IRE instructional strategies to sustainably boost student engagement and motivation.